Tingkat Manajemen Laba pada Perusahaan Agribisnis dengan Aset Biologis di Wilayah Asia Setelah Konvergensi IFRS - Octisari, Sully Kemala (E-Jurnal Akuntansi; Vol 30 No 5 (2020), 2020)
The method of measuring biological assets is considered to provoke earnings management practices in agribusiness companies, especially in companies that have adopted IFRS in full. This study aims to examine whether agribusiness companies that have adopted IFRS in full will have a higher level of earnings management when compared to other industries. The sample of this study was taken from agribusiness companies in several Asian countries that are still in the IFRS convergence process. The research hypothesis was analyzed by independent t test to test the level of earnings management in the period before and after the convergence of IFRS. The results showed that agribusiness companies in the Asian region had higher average earnings management in the period after the IFRS convergence, when compared to before the IFRS convergence. Keywords: Biological Asset; IFRS; Fair Value; Earning Management.